Implementation of Project Based Learning with Practicum Methods to Improve Critical Thinking Skills of Students - Fahma, Dika Isnaini; Krisdiana, Ika; Trianawati, Eny (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2023)
One of the main goals of going to school is to improve students' ability to think critically, so that they can make rational decisions about what to do or what to believe. Students at the junior high school (SMP) level are expected to be able to think deductively, analyze and synthesize, think reflectively and abstractly, and be able to solve various problems. The education system has a top priority, namely educating students to learn and think critically. One way to improve critical thinking skills is to use the Project Based Learning (PjBL) learning model using the practicum method. This research was conducted to improve students' critical thinking skills in science subjects. The type of research carried out was classroom action research consisting of two cycles. Each cycle consists of planning stages, implementation stages, and evaluation and reflection stages. The reflection results in cycle I will be improved in cycle II. The results of this study are that there is a significant increase in students' critical thinking skills through the application of the Project Based Learning (PjBL) learning model with the practicum method in class VII D SMP Negeri 1 Bagor academic year 2022/2023 by 48% of students who pass in cycle 1 and increased to 84% in cycle 2.